Public Awareness, Perceptions, and Attitudes Toward Renewable Energy Adoption in the Philippines: Insights for Strategic Policy Development - Catubay, Arvin T.; Cristobal, Jomel R.; Malang, Bernandino P.; Malang, Jocelyn DS. (Future Science / FSH-PH Publications, 2024)
The Philippines currently depends heavily on fossil fuels, which are vulnerable to price fluctuations. In response, the 2023-2050 Philippine Energy Plan sets ambitious targets to increase the share of renewable energy in the capacity mix: 35% by 2030 and 50% by 2040. Achieving these targets require more than just policy—it needs public understanding and support. This study examines public awareness, perceptions, and attitudes toward renewable energy in the Philippines, specifically among respondents from Metro Manila, Bulacan, Cavite, and Laguna. Through a structured survey of 386 participants, we assessed familiarity with renewable sources like biomass, geothermal, solar, hydro, ocean and wind, finding that while 70% are generally aware of these sources, only 30% know about local projects or government initiatives. The survey results show strong support for renewable energy’s environmental benefits, with 67% of respondents in favor, though 69% express concerns about high initial costs, and 57% are wary of reliability issues. Using statistical analysis, we found that age significantly affects awareness levels (p < 0.001), while gender, income, and location have minimal influence. These insights underline the need for public engagement to support the goals of the 2023-2050 Philippine Energy Plan. Our findings suggest that more targeted education, financial incentives, and community involvement could boost public support and address perceived barriers, providing valuable direction for policymakers to enhance renewable energy adoption across the Philippines.